Psychology: Sexual abuse in children and adolescents in the interior of the country : A statistical approach from the relationship between victims and perpetrator (Legal journal - Research in Legal and Social Sciences, 2017)
The research "Sexual abuse in children and adolescents in the interior of the country: a statistical approach from the relationship between victim and aggressor" arises from a problem that involves a population sector as vulnerable as that of children and adolescents from large geographical areas. and little explored in Paraguay, under the -psychosocially unacceptable- demands of adults, usually close to them, although it is worth saying that, historically, in the past it has become an admissible practice or conduct in many cultures, obviously far from sanctions or seeking justice. Due to the complexity of this issue, the general objective is given: to determine the relationship between children and adolescents victims of sexual abuse and their perpetrators, from the interior of the country, according to the regional statistical records of the Attention Center to Victims, corresponding to fiscal areas IV to X of the Public Ministry, in the first semester of 2010. Through descriptive and inferential statistics, the current investigative work is framed from the quantitative, for which the results are presented and analyzed with the support of recognized computer programs: SPSS 11.5 for Windows, as a database and percentage calculations, and Microsoft Office Excel, as a spreadsheet in the preparation of the tables and figures that illustrate the results. The formal structure of the study is based on international and national technical standards for reporting and scientific articles, which establish its validity and enhance the descriptions discussed in it.
Keywords: interior of the country; relationship; aggressor; Victim; Sexual abuse